The Effectiveness of Systems Thinking Training and Creative Problem-Solving on Social-Emotional Skills in University Students - Babaei, Ali (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to investigate the effectiveness of systems thinking and creative problem-solving training on social-emotional skills among first-year undergraduate students at Shahid Chamran University of Ahvaz.Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest structure and a control group. The statistical population consisted of first-year undergraduate students at Shahid Chamran University of Ahvaz during the 2025–2026 academic year. Using purposive sampling, 60 students were selected and randomly assigned into experimental and control groups, with 30 participants in each group. The experimental group participated in a systems thinking and creative problem-solving training program consisting of twelve 90-minute sessions conducted twice weekly, while the control group received no intervention. Data were collected using the Social Emotional Competence Questionnaire developed by Zhou and Ee (2012), which assesses self-awareness, social awareness, self-management, relationship management, and responsible decision-making. Data analysis was performed using IBM SPSS Statistics version 27 through descriptive statistics, multivariate analysis of covariance, and adjusted mean comparisons.Findings: The findings demonstrated a statistically significant difference between the experimental and control groups in overall social-emotional skills after controlling for pretest scores (Wilks’ Lambda = 0.214, F = 34.72, p = 0.001, partial η² = 0.786). Significant improvements were observed in all dimensions of social-emotional skills, including self-awareness (F = 29.64, p = 0.001), social awareness (F = 35.81, p = 0.001), self-management (F = 33.92, p = 0.001), relationship management (F = 38.67, p = 0.001), and responsible decision-making (F = 32.84, p = 0.001). The adjusted mean scores indicated that the experimental group achieved substantially higher posttest scores than the control group across all measured dimensions.Conclusion: The results suggest that systems thinking and creative problem-solving training significantly improve social-emotional skills among university students. The intervention enhanced students’ emotional awareness, interpersonal understanding, emotional regulation, communication abilities, and responsible decision-making capacities.